2020
DOI: 10.1111/jocd.13456
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Instagram and photograph editing on seeking dermatologic care

Abstract: Background Photograph editing has become popular for individuals using social media like Instagram. However, it is unknown if the use of social media and photograph editing applications by young adults has an association with seeking dermatologic care. Aims To assess the frequency of photograph editing among a cohort of young adults using Instagram and the association with seeking dermatologic care. Methods A population‐based survey was administered to undergraduate students from April 2019 to May 2019 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 12 publications
5
19
0
Order By: Relevance
“…In our study, the maximum numbers of participants using social media (83.6%) were between 18 and 24 years of age, which is in concordance with the findings of the previous study 3 as the youth have more inclination towards the use of social media. Similar to the study done by Chen et al, 5 the females outnumbered the males and most of the participants had at least achieved secondary level of education.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, the maximum numbers of participants using social media (83.6%) were between 18 and 24 years of age, which is in concordance with the findings of the previous study 3 as the youth have more inclination towards the use of social media. Similar to the study done by Chen et al, 5 the females outnumbered the males and most of the participants had at least achieved secondary level of education.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings Martel et al also observed similar practices in 88.7% of participants. 3 Furthermore, concurring to the study by Sheldon et al, the time spent on editing a photo was less than 5 minutes. 17 …”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations